Measuring concentration risk for regulatory purposes - Marc Gürtler; Martin Hibbeln; Clemens Vöhringer (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2007)
The measurement of concentration risk in credit portfolios is necessary for the determination of regulatory capital under Pillar 2 of Basel II as well as for managing portfolios and allocating economic capital. Existing multi-factor models that deal with concentration risk are often inconsistent with the Pillar 1 capital requirements. Therefore, we adjust these models to achieve Basel II-compliant results. Within a simulation study we test the impact of sector concentrations on several portfolios and contrast the accuracy of the different models. In this context, we also compare Value at Risk and Expected Shortfall regarding their suitability to assess concentration risk.
Keywords: G21; G28; 330; Concentration Risk; Pillar 2; Multi-Factor Models; Economic Capital; Simulation Study; Value at Risk; Expected Shortfall